2019
DOI: 10.1029/2018jd029380
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Recycling of Surface Precipitation to Landfalling Tropical Cyclone Rainfall: A Modeling Study for Typhoon Utor (2013)

Abstract: Surface evaporation is an important factor in the hydrological cycle. It is unknown however how much the recycling of surface precipitation contributes to rainfall in a landfalling tropical cyclone. In this study, ensemble simulations were performed using the Weather Research and Forecasting model to quantify the contribution of re‐evaporation of surface precipitation to rainfall in Typhoon Utor (2013) during and after its landfall over South China. Two sets of ensemble simulations were conducted, one with all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Stronger TCs produce more averaged total rainfall, larger averaged rain areas, and higher averaged rain rates. M. Liu et al (2019) also showed that TCs with high intensity tended to produce high rainfall rates, especially toward the storm center. Therefore, the sufficient water vapor supply and the increase in both duration after landfall and the increase in storm intensity at landfall are all responsible for the increasing trend in STC precipitation in the southern coastal area of mainland China except over Hainan Island.…”
Section: Characteristics Of Strong and Weak Tc Precipitationmentioning
confidence: 93%
See 1 more Smart Citation
“…Stronger TCs produce more averaged total rainfall, larger averaged rain areas, and higher averaged rain rates. M. Liu et al (2019) also showed that TCs with high intensity tended to produce high rainfall rates, especially toward the storm center. Therefore, the sufficient water vapor supply and the increase in both duration after landfall and the increase in storm intensity at landfall are all responsible for the increasing trend in STC precipitation in the southern coastal area of mainland China except over Hainan Island.…”
Section: Characteristics Of Strong and Weak Tc Precipitationmentioning
confidence: 93%
“…7e) also show increasing trends, particularly in the southeastern coastal area of mainland China, providing more favorable thermodynamic conditions to slow down the weakening of TCs after landfall. Previous studies have demonstrated that the soil moisture and temperature are critical for TC maintenance and TC precipitation over land (Tuleya and Kurihara 1978;Tuleya et al 1984;Tuleya 1994;Shen et al 2002;Zhang et al 2011;L. Liu et al 2019).…”
Section: Characteristics Of Strong and Weak Tc Precipitationmentioning
confidence: 99%
“…As shown in Tuleya (1994), warm land surface and high soil moisture are favorable for surface enthalpy flux and thus may slow down the weakening of a TC after landfall. Therefore, the increasing trends in land surface temperature and soil moisture provide more favorable surface thermodynamic conditions for TCs to survive longer after their landfall over mainland China (Li and Chen 2005;Park et al 2011;Zhang et al 2011;L. Liu et al 2019).…”
Section: Trend Analysis For the Related Large-scale Environmental Conditionsmentioning
confidence: 99%
“…Previous studies have suggested that evaporation over wet soils is an important (but secondary) factor in precipitation during and after landfall of tropical systems (e.g., Trenberth et al 2007). Liu et al (2019) also showed that evaporation of rainfall was a secondary but nonnegligible effect contributing to 15%-20% of the total rainfall within 100 km of the center of Typhoon Utor (2013).…”
Section: Introductionmentioning
confidence: 99%